Faktor-Faktor yang Memengaruhi Pertumbuhan Laba pada Subsektor Perbankan yang Terdaftar di Bursa Efek Indonesia - Fadia Aini Winarno; Feny Fidyah; Astried Permanasari (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Net banking profits declined in 2020 compared to the previous year due to the slowdown in the real and corporate sectors during the COVID-19 pandemic. In 2021, banking performance began to recover with a consistent upward trend in net profits until 2024. However, the growth rate of profits slowed after reaching its peak in 2022, indicating that banks are struggling to maintain their profit growth. The purpose of this study is to analyze the effect of non-performing loans, loan to deposit ratio, return on assets, operating expenses on operating income, and capital adequacy ratio on profit growth in the banking sub-sector listed on the Indonesia Stock Exchange for the period 2020-2024. This is a quantitative study using multiple linear regression analysis. The data used are secondary data from company annual reports, comprising 195 samples, using purposive sampling. The testing tool used is SPSS version 27. The results show that the capital adequacy ratio has a positive effect on profit growth, while non-performing loans, loan-to- deposit ratio, return on assets, and operational expenses relative to operational income do not have an effect on profit growth.